2014
DOI: 10.1007/s00394-014-0757-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green tea extract supplementation on exercise-induced oxidative stress parameters in male sprinters

Abstract: BackgroundAlthough research suggests that antioxidant supplementation can protect against exercise-induced muscle damage and oxidative stress, also delayed post-exercise muscle recovery and hindered adaptation to training were reported in the supplemented athletes. PurposeThe purpose of the study was to evaluate the effects of green tea extract (GTE) supplementation on selected blood markers of oxidative stress and muscle damage in sprinters during preparatory phase of their training cycle.MethodsSixteen sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 42 publications
5
108
2
8
Order By: Relevance
“…The results from recent studies have shown that green tea catechins can affect levels of ROS [79][80][81][82], increase levels of antioxidants [83][84][85][86], decrease levels of inflammatory substances [87,88], and increase TAC (TAS) [84,86,87]. An excellent summary of earlier studies that measured ROS and TAC can be found in a chapter by Serafini et al 2011 [67].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The results from recent studies have shown that green tea catechins can affect levels of ROS [79][80][81][82], increase levels of antioxidants [83][84][85][86], decrease levels of inflammatory substances [87,88], and increase TAC (TAS) [84,86,87]. An excellent summary of earlier studies that measured ROS and TAC can be found in a chapter by Serafini et al 2011 [67].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…SOD plays a crucial action in dismutation of superoxide radicals to H 2 O and oxygen. On the other hand, CAT protects the cells from toxic effects of ROS by transforming H 2 O 2 to H 2 O and O 2 [17]. In this respect, numerous studies have reported that castor oil-induced diarrhea causes depletion of antioxidant activities of SOD, CAT, and GPx, which explains the overproduction of ROS [18].…”
Section: Castor Oil-induced Diarrhea Associated With Oxidative Stressmentioning
confidence: 99%
“…Hammouda, Chaouachi, Ferchichi, Kallel, & Souissi ()) proved a significant increase in blood lactate and an increase in biochemical markers of muscle damage (i.e., creatine kinase (CK) and LDH) and lipid profile during YYIRT. Although, research suggests that antioxidant supplementation has a potent role in postexercise recovery in athletes (Jówko et al., ). Hence, elite athletes are more vulnerable, than a sedentary person, to physical performance altered and physiological responses due to stress caused by free radical production (Hammouda et al., ; Prahalathan, Saravanakumar, & Raja, ).…”
Section: Introductionmentioning
confidence: 99%